Interpretation of the Availability of Springs in Labuang Rano Village with a Geophysical Approach - Syarifullah Bundang; George Belly Sahetapy; Dian Dwi Apriliyani Arsdinand; Firman (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Geologically speaking, Labuang Rano Village, Mamuju City area is composed of rocks from the Adang Volcano Formation. Based on the results of the site survey, it was found that there is a spring with a slight discharge. The emergence of these springs is not yet known, so further analysis is needed. An approach used to determine subsurface conditions is the geophysical approach, especially the geoelectric method. This study aims to analyse the subsurface geological conditions using geoelectric to find the factors that influence the emergence of springs. Geoelectrical measurements, observations of rock outcrops, and the findings of previous research are used as data sources. The results of the analysis show that the subsurface geological conditions consist of 3 layers. The topmost layer is tuff rock, the 2nd layer is volcanic breccia and the 3rd layer is andesite rock. Based on the resistivity cross-section, it can be seen that there is a fracture that cuts vertically in the tufa rock layer from a depth of 13 m to the surface in a northeast-southwest direction. Thus, it can be concluded that the emergence of springs at the study site was caused by a fracture that cut the tufa rock layers vertically from a depth of 13 to the surface. The fracture which is the medium for groundwater to emerge onto the land surface forms a spring.